Nuances of meaning transitive verb synonym in affixes meN-i in Indonesian - Ranti Permatasari; Ngusman Abdul Manaf; Novia Juita (Fakultas Ilmu Pendidikan UNP)
Understanding of the meaning in language to communicate is very important for language speakers. A speaker who does not understand the benefits of the language can lead to errors when communicating understanding. Moreover, the words used are synonyms. Some studies related to synonymy shows that different forms will have a different meaning. The purpose of this study is to explain the nuances of a transitive verb affixes meN-, -i partner meaning synonymous in Indonesian. This type of research is qualitative descriptive method. Of the 69 data obtained from various sources, there are six pairs of a transitive verb affixes meN-, -i synonymous. The results showed that: (a) not all transitive verbs affixes meN-, -i in Indonesian have a partner that is synonymous; (b) not found transitive verb affixes meN-, -i manifold absolute synonyms; (c) was found transitive verb affixes meN-, -i nuanced meaning both cognitive and emotive meaning. This means that not all of synonyms can be used to replace the partner. Speakers suggested to deepen in understanding the nuances of meaning in synonyms in order to choose the appropriate word.